2023
DOI: 10.1002/ange.202304706
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chiral Diarylmethylamines by Cobalt‐Catalyzed Enantioselective C‐H Alkoxylation

Abstract: Chiral diarylmethylamines (DAMA) are important structural motifs widely present in pharmaceuticals, natural products, and chiral ligands. Herein, we reported a highly enantioselective synthesis of chiral DAMAs via cobalt-catalyzed enantioselective CÀ H alkoxylation strategy. The reaction features easy operation, the use of earth-abundant and cost-efficient cobalt(II) catalyst, and readily available ligand. A range of chiral DAMAs were efficiently synthesized in high yields with excellent enantioselectivities (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…[36,83] Meanwhile, there are stronger exciton effects and electron-phonon couplings in the 2D Sn-based films, and the introduction of bulky A sites results in stronger spin-orbit coupling and Rashba splitting when compared to the 3D perovskites. [84] Therefore, effective observation of carrier behavior in the low-dimensional films becomes more important, in which a variety of spectroscopic analysis techniques are resorted. At present, the main spectroscopic analysis techniques used in low-dimensional Sn-based films include transient fluorescence spectra, time-resolved fluorescence spectra, and femtosecond TAS.…”
Section: Developing Optical Spectroscopic Techniquesmentioning
confidence: 99%
“…[36,83] Meanwhile, there are stronger exciton effects and electron-phonon couplings in the 2D Sn-based films, and the introduction of bulky A sites results in stronger spin-orbit coupling and Rashba splitting when compared to the 3D perovskites. [84] Therefore, effective observation of carrier behavior in the low-dimensional films becomes more important, in which a variety of spectroscopic analysis techniques are resorted. At present, the main spectroscopic analysis techniques used in low-dimensional Sn-based films include transient fluorescence spectra, time-resolved fluorescence spectra, and femtosecond TAS.…”
Section: Developing Optical Spectroscopic Techniquesmentioning
confidence: 99%
“…It has been previously reported that the Suzuki–Miyaura coupling of chiral α-(acylamino)­benzylboronic esters with aryl bromides and chlorides in the presence of a chiral palladium catalyst could provide diarylmethylamide products (Scheme B), while a major limitation is that the products’ enantioselectivity completely depended on the chirality transfer from the presynthesized chiral substrates. Very recently, the asymmetric alkoxylation of picolinamides with alcohol via transition metal-catalyzed enantioselective C–H functionalization enables the synthesis of chiral diarylmethylamides (Scheme C), however, the range of amides skeleton was limited. In principle, the direct construction of chiral C–N bonds is undoubtedly one of the most efficient means to access chiral diarylmethylamides, and seeking appropriate reactants and catalysts to augment the stereoselective methods that enable the construction of such molecules in a C–N bond-forming event is in high demand, particularly under metal-free conditions.…”
Section: Introductionmentioning
confidence: 99%